Characterization of immune response against Mycobacterium marinum infection in the main hematopoietic organ of adult zebrafish (Danio rerio). (February 2020) - Harjula, Sanna-Kaisa E.; Saralahti, Anni K.; Ojanen, Markus J.T.; Rantapero, Tommi; Uusi-Mäkelä, Meri I.E.; Nykter, Matti; Lohi, Olli; Parikka, Mataleena; Rämet, Mika
Abstract: Tuberculosis remains a major global health challenge. To gain information about genes important for defense against tuberculosis, we used a well-established tuberculosis model; Mycobacterium marinum infection in adult zebrafish. To characterize the immunological response to mycobacterial infection at 14 days post infection, we performed a whole-genome level transcriptome analysis using cells from kidney, the main hematopoietic organ of adult zebrafish. Among the upregulated genes, those associated with immune signaling and regulation formed the largest category, whereas the largest group of downregulated genes had a metabolic role. We also performed a forward genetic screen in adult zebrafish and identified a fish line with severely impaired survival during chronic mycobacterial infection. Based on transcriptome analysis, these fish have decreased expression of several immunological genes. Taken together, these results give new information about the genes involved in the defense against mycobacterial infection in zebrafish. Highlights: 201 genes were up- or downregulated at 14 days post zebrafish M. marinum infection. Among upregulated genes, innate immune processes were most enriched. Among downregulated genes, metabolic processes were most enriched. We identified a mutant line with impaired resistance against M. marinum infection. The mutants display deficiency in T cell activation and inflammasome function.